2021
DOI: 10.3389/fimmu.2021.639226
|View full text |Cite
|
Sign up to set email alerts
|

Second Report of Chronic Granulomatous Disease in Jordan: Clinical and Genetic Description of 31 Patients From 21 Different Families, Including Families From Lybia and Iraq

Abstract: Chronic granulomatous Disease (CGD) is a rare innate immunodeficiency disorder caused by mutations in one of the six genes (CYBA, CYBB, NCF1, NCF2, NCF4, and CYBC1/EROS) encoding the superoxide-producing nicotinamide adenine dinucleotide phosphate (NADPH)—oxidase complex in phagocytes. In the Western population, the most prevalent form of CGD (about two-thirds of all cases) is the X-linked form (X-CGD) caused by mutations in CYBB. The autosomal recessive forms (AR-CGD), due to mutations in the other genes, col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Intriguingly, it is most common in East Asians (Chinese, Japanese, and Koreans) [31][32][33][34][35][36][37][38]. The mutation appears much less common in large cohorts from Europe and America, or even in regions with high levels of parental consanguinity such as the Middle East or India [10,15,[42][43][44][45][46][47][48][49][50][51][52][53][54][55]. The identi ed mutations in the CYBA gene reveal its allelic heterogeneity; there is no commonly affected allele or hot spots worldwide [9].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, it is most common in East Asians (Chinese, Japanese, and Koreans) [31][32][33][34][35][36][37][38]. The mutation appears much less common in large cohorts from Europe and America, or even in regions with high levels of parental consanguinity such as the Middle East or India [10,15,[42][43][44][45][46][47][48][49][50][51][52][53][54][55]. The identi ed mutations in the CYBA gene reveal its allelic heterogeneity; there is no commonly affected allele or hot spots worldwide [9].…”
Section: Discussionmentioning
confidence: 99%
“…Also, many studies done by Wolach et al (20) , El Hawary et al (21) and Fattahi et al (22) reported consanguineous marriages in 82.1%, 77.4% and 64% respectively. Similarly, the study of Bakri et al (27) investigated the clinical and molecular features of 31 CGD patients, 22 Jordanian, 7 Libyan, and 2 Iraqi from 21 different families. All patients except 9 were children of consanguineous parents (70.9%).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the high frequency of the other recessive CGD mutations is not known. 1(1) [1,37,101,102 ] unpubl. [1,26,37,39,101] unpubl.…”
Section: /9/21mentioning
confidence: 99%